Total contact casting in treatment of diabetic plantar ulcers. Controlled clinical trial - M J Mueller; J E Diamond; D R Sinacore; A Delitto; V P Blair, 3rd; D A Drury; S J Rose (Diabetes care, 1989)
Total contact casting in treatment of diabetic plantar ulcers. Controlled clinical trial. M J Mueller , J E Diamond , D R Sinacore , A Delitto , V P Blair, 3rd , D A Drury and S J Rose Irene Walter Johnson Rehabilitation Institute, Washington University School of Medicine, St. Louis, Missouri 63110. Abstract This study compared the treatment of total contact casting (TCC) with traditional dressing treatment (TDT) in the management of diabetic plantar ulcers. Forty patients with diabetes mellitus and a plantar ulcer but with no gross infection, osteomyelitis, or gangrene were randomly assigned to the TCC group (n = 21) or TDT group (n = 19). Age, sex, ratio of insulin-dependent diabetes mellitus to non-insulin-dependent diabetes mellitus, duration of diabetes mellitus, vascular status, size and duration of ulcer, and sensation were not significantly different between groups (P greater than .05). In the experimental group, TCC was applied on the initial visit, and subjects were instructed to limit ambulation to approximately 33% of their usual activity. Subjects in the control group were prescribed dressing changes and accommodative footwear and were instructed to avoid bearing weight on the involved extremity. Ulcers were considered healed if they showed complete skin closure with no drainage. Ulcers were considered not healed if they showed no decrease in size by 6 wk or if infection developed that required hospitalization. In the TCC group, 19 of 21 ulcers healed in 42 +/- 29 days; in the TDT group, 6 of 19 ulcers healed in 65 +/- 29 days. Significantly more ulcers healed (chi 2 = 12.4, P less than .05) and fewer infections developed (chi 2 = 4.1, P less than .05) in the TCC group. We conclude TCC is a successful method of treating diabetic plantar ulcers but requires careful application, close follow-up, and patient compliance with scheduled appointments to minimize complications.